(untitled) (Swiss Medical Weekly, 2019)
AIM OF THE STUDY The aim of this multicentre, prospective, open, nonrandomised clinical trial was to demonstrate the clinical efficiency and outcomes of cochlear implants (CIs) in adult patients with post-lingual single-sided deafness (SSD). METHODS A group of five left and five right SSD participants were investigated with various clinical tests and questionnaires before and 12 months after CI activation. Changes in hearing thresholds, speech understanding in noise, sound localisation, tinnitus (Tinnitus Handicap Inventory; THI), subjective hearing ability (Speech, Spatial and Qualities of Hearing Scale; SSQ), and quality of life (WHOQOL-BREF) were assessed. In addition, the pre- and postoperative results of the SSD patients were compared with an age- and gender-matched normal hearing control group. RESULTS Surgery was uncomplicated in all patients. Two years after implantation, 9 of the 10 patients used their CI regularly for an average of more than 11 hours a day. A significant improvement in speech understanding in noise measured in the sound field using the Oldenburg sentence test could be demonstrated in the two situations in which patients with SSD experience the greatest difficulty: speech from the front and noise at the healthy ear, and speech to the implanted ear and noise from the front. The sound localisation test showed significant improvement of the mean localisation error and the root mean square error after CI activation. Furthermore, a significant reduction of the THI was measured, and the SSQ showed a significant improvement in the subscale speech comprehension and in the subscale spatial hearing. Also, quality of life measured with the WHOQOL-BREF showed a general improvement, which was significant in the global subscale. For this questionnaire, there was no significant difference between the normal-hearing control group and the patients after 12 months of CI use. CONCLUSION This study confirmed the clinical benefit of cochlear implantation in patients with SSD. The significant improvement of speech understanding in noise, sound localisation, tinnitus perception, subjective hearing ability, and in particular the improved quality of life support the recommendation that patients with recently acquired SSD should be offered a CI. (Clinical trial registration number on clinicaltrial.gov: NCT01749592)